2012
DOI: 10.1111/j.1744-7917.2011.01500.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of host, temperature and relative humidity on competitive displacement of two invasive Bemisia tabaci biotypes [Q and B]

Abstract: Bemisia tabaci shifted unexpectedly in China from a predominance of B biotype to Q biotype during 2005–2008. This observation stimulated an interest in investigating whether environmental factors, including host, temperature and relative humidity (RH) could possibly explain the observed shift in biotypes distribution. Results indicated that all three parameters examined influenced biotype survivability. The percentage of B biotype, when reared together on pepper plants with the Q biotype, decreased significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…The overall survival of all populations from egg to adult eclosion was highest on eggplant (80-98%) and lowest on pepper (0.6-20%). Similar results have been reported in previous studies [15,29,34,37]. Again, this result confirmed that host plant had the foremost effect on the survival of whitefly immatures.…”
Section: Discussionsupporting
confidence: 92%
“…The overall survival of all populations from egg to adult eclosion was highest on eggplant (80-98%) and lowest on pepper (0.6-20%). Similar results have been reported in previous studies [15,29,34,37]. Again, this result confirmed that host plant had the foremost effect on the survival of whitefly immatures.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, an invasive Q1 population reported in China has displaced the previously invasive B biotype in at least certain locations, particularly in certain vegetable crops [92]. To what extent the two lineages have biological and ecological differences remains to be further studied [116]; they originate from proximal geographies and apparently both possess high inherent, differential, resistance to presently used insecticides in agricultural production [50, 113, 117], and which could logically have been a driving force behind their establishment outside their indigenous zones that contain highly managed agricultural systems.…”
Section: Discussionmentioning
confidence: 99%
“…4 and 5), for example, were carried out under warm (268 6 28C) conditions with no climatic variation. MEAM1 and MED respond differently to temperature variation, however, with MED being more tolerant than MEAM1 of temperature extremes (Elbaz et al 2011, Chu et al 2012b. Although MED now dominates agricultural systems, China contains a heterogeneous mix of landscapes that vary in their abiotic, biotic, and anthropogenic (i.e., insecticide use) conditions.…”
Section: Discussionmentioning
confidence: 99%
“…They also differ in their susceptibility to insecticides, with MED generally showing greater tolerance of neonicotinoids and other insecticides (Crowder et al 2010a, Jones et al 2011. The outcome of MEAM1-MED interactions can be affected by host plant and abiotic factors such as temperature and humidity (Chu et al 2012b); in general, however, the greater ability of MEAM1 than MED to mate with conspecifics in mixed populations and greater effort devoted by MEAM1 to reproduction leads to the competitive exclusion of MED in laboratory experiments (Pascual and Callejas 2004, Pascual 2006, Crowder et al 2010a, b, Tsueda and Tsuchida 2011.…”
Section: Introductionmentioning
confidence: 99%